Navigating Design Spaces: Finding Designs, Design Collections, and Design Subspaces. (June 2022) - Garcia, Sara; Leitão, António
Generative design systems can generate a wide panoply of solutions, from which designers search for those that best suit their interests. However, without guidance, this search can be highly inefficient, and many interesting solutions may remain unexplored. This problem is mitigated with automated exploration methods. Still, the ones typically provided by generative design tools are mostly based on black-box methods that drastically reduce the role of the designer, while more straightforward white-box mechanisms are dispersedly found in specific applications. This paper proposes the Navigator tool, which gathers a set of white-box mechanisms that automate the generation of default, random, similar and hybrid designs and design subspaces, while also supporting the generation of design collections. The proposed mechanisms were tested with two generative systems that create, respectively, tower and chair designs. We expect that, by providing understandable mechanisms for navigating design spaces, designers can become more engaged in the search process.